PERMUTATIONS OF LENGTH N THAT AVOID PATTERN OF LENGTH FOUR - Tarakolo, Seplin
Permutation is called to contain a pattern , if has at least a subsequence whose elements correspond with elements of . Let be a permutation with c and d as four entries in (that follow in this order from left to right, but are not necessarily consecutive). If , then is called form a -pattern. If there are no four entries in that form -pattern, then is called - avoiding. In this project, we review how to determine the number of permutations of length that avoid pattern of length four and a special permutation that does not contain one of the pattern of length four which is called permutation two-stack sortable.